Effect of thermocycling on the flexural and impact strength of urethane-based and high-impact denture base resins - Machado, Ana Lucia [UNESP]; Puckett, Aaron D.; Breeding, Larry C.; Wady, Amanda Fucci [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2012)
Objective: Mechanical properties of the acrylic resins used for denture fabrication may be influenced by water and temperature. Thus, the aim of this study was to evaluate the effect of thermocycling on the flexural and impact strength of a high-impact (Lucitone 199) and a urethane-based denture material (Eclipse).Materials and methods: Flexural strength (64 x 10 x 3.3 mm) and impact strength (60 x 6 x 4 mm) specimens were made following the manufacturers' instructions and assigned to two groups (n = 10): control (C) - not thermocycled - and T - thermocycled (5000 cycles between 5 and 55 degrees C). Specimens were submitted to three-point bending and Charpy impact tests.Results: Flexural strength (MPa) and impact strength (kJ/m(2)) data were analysed with two-way ANOVA (p = 0.05). The flexural strength of material Eclipse (C, 136.5; T, 130.7) was significantly higher than that of resin Lucitone 550 (C, 99.4; T, 90.1). Material Eclipse exhibited significantly higher impact strength (C, 6.9; T, 5.3) than the resin Lucitone 550 (C, 3.5; T, 3.0). For both materials, a significant decrease in flexural and impact strengths was observed when the specimens were thermocycled.Conclusion: Flexural and impact strengths were higher for Eclipse than for Lucitone 550, in both groups. Thermocycling decreased the flexural and impact strengths of Eclipse and Lucitone 550.
Keywords: denture base acrylic resins; flexural strength; impact strength; thermocycling